Tunable, amine-functionalized porous silica catalyst for CO2 transformation into cyclic organic carbonates at atmospheric pressure - Gorai, Twinkle; Thanasekar, Chandragopal; Kumar, Pawan; Babu, Athira; Kurungot, Sreekumar; Vinod, C. P. (Chemistry-A European Journal, 2025)
A silica catalyst with characteristic features of broad pore size distribution, large pore width and tunable basic sites was synthesized by a one-step green co-condensation synthesis method analogous to SBA-15 synthesis. The surface chemical features of the above catalyst were explored by XPS, N-2 and CO2 adsorption and desorption experiments. The catalyst showed 90% conversion of styrene oxide (SO) with nearly complete selectivity toward styrene carbonate (SC) in 7 hours under a solvent-free condition at a temperature of 120 degrees C with the aid of co-catalyst tetrabutylammonium bromide (TBAB). Moreover, the catalyst demonstrates versatility with various epoxide substrates, providing valuable insights into the cycloaddition reaction under ambient pressure conditions involving carbon dioxide. The mechanistic details of the catalytic conversion were investigated by the in-situ DRIFT studies and reported here.
Keywords: CO2 fixation; cyclic organic carbonates; heterogeneous catalysis; in-situ FTIR

Orthogonally Engineered Redox-Active Polyimide-Carbon Nanotube Hybrids for Long-Life Lithium-Ion Battery Cathode - Thanasekar, Chandragopal; Javaregowda, Bharathkumar H.; Veer, Sairam Dnyaneshwar; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2026)
The diverse structural tunability and engineered electronic properties of organic polymers have sparked significant interest in their use as cathode materials for lithium-ion storage. Recent advances suggest that organic cathodes can serve as promising alternatives to conventional metal oxide counterparts due to their elemental abundance, safety, and high theoretical capacity. However, developing cathode materials that simultaneously exhibit high specific capacity, long cycle life, and excellent rate performance remains a critical challenge. In this study, the synthesis and application of a redox-active polyimide based on orthogonally positioned, active site-rich mellitic trianhydride (MTA) and naphthalene diimide (NDI), integrated with multi-walled carbon nanotubes (MWCNTs), referred to as MTA-NDI@CNT are reported. The pristine MTA-NDI polymer demonstrates a specific capacity of 60 mAh g-1 at a current density of 200 mA g-1 and exhibits remarkable cycling stability over 20 000 cycles. Upon hybridisation with CNT (10 wt.%), the composite (MTA-NDI@CNT) delivers a nearly threefold enhancement in specific capacity, reaching 170 mAh g-1 at 500 mA g-1, along with stable cycling performance over 1300 cycles and 60.5% capacity retention.
Keywords: cathode; CNT; lithium-ion battery; orthogonality; Polyimide